2004
DOI: 10.1111/j.1365-2885.2004.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and pharmacokinetics of nonsteroidal anti‐inflammatory drugs in species of veterinary interest

Abstract: This review summarises selected aspects of the pharmacokinetics (PK) and pharmacodynamics (PD) of nonsteroidal anti-inflammatory drugs (NSAIDs). It is not intended to be comprehensive, in that it covers neither minor species nor several important aspects of NSAID PD. The limited objective of the review is to summarise those aspects of NSAID PK and PD, which are important to an understanding of PK-PD integration and PK-PD modelling (the subject of the next review in this issue). The general features of NSAID PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
274
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(290 citation statements)
references
References 77 publications
(80 reference statements)
7
274
3
6
Order By: Relevance
“…They exert these effects mostly through inhibiting the production of prostaglandins (PGs) and leukotrienes (LTs) by the cyclo-oxygenase (COX) and 5-lipoxygenase (5-LOX) enzymes, respectively. [33][34][35] Most NSAIDs primarily inhibit the activity of COX enzymes. Although some also inhibit LOX enzymes, for currently licensed feline drugs this is generally short-lived in comparison with COX inhibition, and evidence of additional clinical efficacy from this is lacking.…”
Section: Nsaids and Cyclo-oxygenase/ Lipoxygenase Inhibitionmentioning
confidence: 99%
“…They exert these effects mostly through inhibiting the production of prostaglandins (PGs) and leukotrienes (LTs) by the cyclo-oxygenase (COX) and 5-lipoxygenase (5-LOX) enzymes, respectively. [33][34][35] Most NSAIDs primarily inhibit the activity of COX enzymes. Although some also inhibit LOX enzymes, for currently licensed feline drugs this is generally short-lived in comparison with COX inhibition, and evidence of additional clinical efficacy from this is lacking.…”
Section: Nsaids and Cyclo-oxygenase/ Lipoxygenase Inhibitionmentioning
confidence: 99%
“…As mentioned previously, the majority of NSAIDs are poorly selective, inhibiting COX-1 and COX-2 equally (Fitzpatrick et al, 2004;Vicente, 2004). Drugs that inhibit COX-1 are considered the main causative of stomach lesions, because this enzyme is generally -but not exclusively -responsible for the above mentioned adverse effects on the gastrointestinal tract (Jones & Blikslager, 2001;Lees et al, 2004;Videla & Andrews, 2009). Although the ulcer-causing potential may vary among NSAIDs, a study of rat stomachs with normal mucosa after acid challenge showed that inhibition of both cyclooxygenases causes gastrointestinal injury; however, inhibition of only one of these enzymes did not have this effect (Gretzer et al, 2001).…”
Section: Gastric Ulcersmentioning
confidence: 99%
“…Furthermore, administering NSAIDs on an empty stomach may result in local gastric irritation. Therefore, these drugs should be administered with food when given orally (Mathews, 2002;Lees et al, 2004;Monreal et al, 2004). The site of NSAID-induced ulcers in the stomach of horses remains controversial.…”
Section: Gastric Ulcersmentioning
confidence: 99%
“…The cancer drug 6-azauridine can be used in humans for long periods; but in dogs small doses produce potentially lethal results in a few days (Weatherall 1982). Phenylbutazone works through the body slowly in humans; but in dogs it disappears in hours (Lees et al 2004). The list of substances and their effects in different species is immeasurable.…”
Section: Rationale For Ending Animal Usementioning
confidence: 99%